Case Report: A Chronological Combination Treatment of Icotinib, Osimertinib, and Crizotinib on Lung Adenocarcinoma Guided by Serial Genetic Tests of Circulating Tumor DNA and Sediment Cell Genomic DNA From Pleural Effusion - Miao, Zhihua; Mu, Tianhao; Liu, Longying; Rao, Jingjie; Jin, Min; Wang, Zhizheng; Wang, Hui; Lu, Chao; Gong, Xiaolin; Zheng, Dongcai; Zheng, Daoming; Li, Xin; et al. (Frontiers in Oncology, 2020)
Precision medicine has been getting more attention in lung cancer treatment. Here, we report an unusual case of a 71-year-old Chinese male patient with poorly differentiated lung adenocarcinoma with lymph node metastasis. A 5 years' treatment history of this patient is reported. By serial genetic tests of circulating tumor DNA (ctDNA) from peripheral blood and sediment cell genomic DNA (PE-sDNA) from pleural effusion, a novel chronological combination treatment of icotinib, osimertinib, and crizotinib was adopted for the present genetic mutations, including EGFR exon 19 deletion, EGFR p.T790M, and MET amplification.